2010
DOI: 10.4049/jimmunol.0900459
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A–Producing γδ T and Th17 Lymphocytes Mediate Lung Inflammation but Not Fibrosis in Experimental Silicosis

Abstract: IL-17–producing T lymphocytes play a crucial role in inflammation, but their possible implication in fibrosis remains to be explored. In this study, we examined the involvement of these cells in a mouse model of lung inflammation and fibrosis induced by silica particles. Upregulation of IL-17A was associated with the development of experimental silicosis, but this response was markedly reduced in athymic, γδ T cell-deficient or CD4+ T cell-depleted mice. In addition, γδ T lymphocytes and CD4+ T cells, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
107
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 74 publications
12
107
0
1
Order By: Relevance
“…At higher concentrations and more long-term models, such as hypersensitivity pneumonitis, 24,41 IL-17 may lead to a more protracted inflammatory state. In shorter-term "single-hit" models, such as bleomycin and silica, 48 in which IL-17 production is limited, IL-17 may have a less inflammatory role. Furthermore, IL-17 is capable of inducing all three CXCR-3 family members (ie, CXCL9, CXCL10, and CXCL11) because they have transcription factor-binding patterns associated with IL-17-induced genes.…”
Section: Discussionmentioning
confidence: 99%
“…At higher concentrations and more long-term models, such as hypersensitivity pneumonitis, 24,41 IL-17 may lead to a more protracted inflammatory state. In shorter-term "single-hit" models, such as bleomycin and silica, 48 in which IL-17 production is limited, IL-17 may have a less inflammatory role. Furthermore, IL-17 is capable of inducing all three CXCR-3 family members (ie, CXCL9, CXCL10, and CXCL11) because they have transcription factor-binding patterns associated with IL-17-induced genes.…”
Section: Discussionmentioning
confidence: 99%
“…Infected lung injury causes production of IL-17-promoting cytokines, such as TGF-b, IL-6, TNF-a, and IL-1b, in the inflamed lung (1). In addition, Th1, Th17, and neutrophils are important in the pathogenesis of autoimmune inflammation (15)(16)(17). Recently, some studies have examined the function of IL-17 in innate immunity, including in infected lungs (18,19).…”
mentioning
confidence: 99%
“…The number of bacteria in the inoculating dose was confirmed by plating. The LD 50 Preparation of bronchoalveolar lavage fluid and lung single-cell suspensions Bronchoalveolar lavage fluid (BALF) was collected and harvested as previously described (17). In brief, the trachea was exposed by producing a midline incision and then cannulated with a sterile 22-gauge Abbocath-T catheter.…”
mentioning
confidence: 99%
“…Although IL-23 was initially thought to mediate the T h 17 response, it was later found that it regulated the terminal differentiation of committed T h 17 cells and their expansion, migration, survival and maintenance (41). Also, IL-23 was required for the recruitment of T h 17 cells and mediated lung inflammation, as shown in an experimental silicosis (42). Therefore, it is likely that both the neutralization and deficiency of IL-23 ameliorate the disease by affecting the T h 17 memory/effector response.…”
Section: Discussionmentioning
confidence: 99%